1962
DOI: 10.1071/bi9620371
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin and Erythrocyte Potassium Types in Sheep and their Influence on Oxygen Dissociation and Haemoglobin Denaturation

Abstract: SummaryThe influence of haemoglobin type and erythrocyte potassium concentration on oxygen dissociation curves and rate of denaturation of haemoglobin by alkali have been studied in Southdown sheep.A significant difference has been found between haemoglobin types in respect to their oxygen dissociation curves and rate of alkali denaturation.A significant difference was found between the oxygen dissociation curves of high potassium (HK) and low potassiu~ (LK) sheep. No significant difference was found between H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1967
1967
1977
1977

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…It has been claimed that, on average, HK red cells have a higher dry-matter content and specific gravity than LK-type red cells, but the correlation was only very weak (Mounib & Evans,1g59). In studies using only a few animals, Dawson & Evans (1962) found a significant difference between the two cell types in their oxygen dissociation curves, that for HK lying to the left of that for LK blood. Koch (1963) noticed that in LK-type Merino sheep, a breed noted for having very low redcell potassium levels, the glucose 6-phosphate dehydrogenase values were also lower than in the Southdown breed.…”
Section: ( 5 ) Possible S@ufiance Of Potassium Polymorphismmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been claimed that, on average, HK red cells have a higher dry-matter content and specific gravity than LK-type red cells, but the correlation was only very weak (Mounib & Evans,1g59). In studies using only a few animals, Dawson & Evans (1962) found a significant difference between the two cell types in their oxygen dissociation curves, that for HK lying to the left of that for LK blood. Koch (1963) noticed that in LK-type Merino sheep, a breed noted for having very low redcell potassium levels, the glucose 6-phosphate dehydrogenase values were also lower than in the Southdown breed.…”
Section: ( 5 ) Possible S@ufiance Of Potassium Polymorphismmentioning
confidence: 93%
“…Another speculative suggestion as to a possible adaptive value of the haemoglobin types in sheep was put forward by Manwell & Baker (1970). They argued that since HbB is more easily denatured and dissociated into subunits, and hence is less stable than HbA (Dawson & Evans, 1962;Shreffler & Vinograd, 1962;Breathnach, 1964), sheep with the latter haemoglobin may have some advantage over HbB-type sheep because less of their amino-acid intake and energy production has to be used for maintenance of the circulating haemoglobin levels. Manwell & Baker suggested that, since the PA haemoglobin chain has only two methionine residues and thePC chain none compared with the PB chain which has 3 methionine residues, sheep with the gene for HbA, under normal situations, can spare more methionine for the production of other proteins.…”
Section: ( 5 ) Possible Signijicance Of Haemoglobin Polymorphismmentioning
confidence: 99%
“…Sheep haemoglobins A and B differ from each other in their oxygen dissociation characteristics, Hb A having a greater affinity for oxygen than Hb B (Huisman, van Vliet, and Sebens 1958;Dawson and Evans 1962). Addition of GSH to human blood shifts the oxygen dissociation curve to the right, i.e.…”
Section: (E) Relationships Between Erythrocyte Gsh Levels and The Parmentioning
confidence: 99%
“…This type has a slightly lower whole blood oxygen affinity than the high potassium erythrocyte type (Dawson and Evans, 1962). The right common carotid arteries were permanently exteriorized.…”
Section: Methodsmentioning
confidence: 99%
“…In domestic sheep there exist two genetically determined types of haemoglobin (Evans, King, Cohen, Harris and Warren, 1956), which have different oxygen affinities (Huisman, van Vliet and Sebens, 1958;Meschia, Naughton, Battaglia, Hellegers and Barron, 1961;Dawson and Evans, 1962). There are variations in the gene frequencies of these haemoglobins associated with variations in the environment Warren, 1958a, 1958ii;Evans and Blunt, 1961), indicating possible adaptive significance, i.e., sheep possessing one of the haemoglobins may have some form of advantage in certain environments over sheep possessing the other haemoglobin.…”
Section: Introductionmentioning
confidence: 99%